The #Metoo Movement and Judges' Gender Gap in Decisions - Xiqian Cai; Shuai Chen; Zhengquan Cheng (Institute of Labor Economics (IZA), 2024)
Gender inequality and discrimination still persist, even though the gender gap in the labor market has been gradually decreasing. This study examines the effect of the #MeToo movement on judges' gender gap in their vital labor market outcome–judicial decisions on randomly assigned legal cases in China. We apply a difference-in-differences approach to unique verdict data including rich textual information on characteristics of cases and judges, and compare changes in sentences of judges of a different gender after the movement. We find that female judges made more severe decisions post-movement, which almost closed the gender gap. Moreover, we explore a potential mechanism of gender norms, documenting evidence for improved awareness of gender equality among women following the movement and stronger effects on judges' gender gap reduction in regions with higher (awareness of) gender equality. This implies that female judges became willing to stand out and speak up, converging to their male counterparts after the #MeToo movement.
Keywords: J16; K14; O12; P35; D63; 330; judicial decision; inequality; gender gap; #MeToo movement; crime; machine learning